THE DIFFERENCE OF STUDENTS’ ACHIEVEMENT IN MATHEMATICS BY USING GUIDED-DISCOVERY LEARNING MODEL AND COOPERATIVE LEARNING MODEL JIGSAW TYPE - Anna Angela Sitinjak; Herman Mawengkang (IKIP Siliwangi and I-MES, 2018)
The type of this study is a quasi-experiment study with its purpose to know any difference in students’ achievement in mathematics which using the model of guided discovery learning with cooperative learning model JIGSAW type. The population of this study is all students in SMA N 3 P. Siantar. The sampling technique applied was cluster random sampling. The experimental class I that chosen is X-1 consisted of 36 students, meanwhile, the experimental class II that chosen is X-6 consisted of 36 students. The instrument used to measure the students’ mathematics achievement was an essay test. The normality test used was Lilliefor’s test, get that data is normal and the homogeneity test by using Fisher test, get that data is homogeny. The data analysis technique was t-test at the level of significance α = 5%.The study result showed that there is the difference of students’ achievement in mathematics which using the guided discovery learning model with cooperative learning model JIGSAW type in grade X SMA N 3 P. Siantar where obtained tcalculation = 2.504 at a = 0.05 and ttable = t(0.975,70)= 1.995, then tcalculation = ttable